TRIM59 Protects Mice From Sepsis by Regulating Inflammation and Phagocytosis in Macrophages - Jin, Zheng; Zhu, Zhenhua; Liu, Shanshan; Hou, Yuyang; Tang, Mengyan; Zhu, Pei; Tian, Yuan; Li, Dong; Yan, Dongmei; Zhu, Xun (Frontiers in Immunology, 2020)
Sepsis is associated with bacterial invasion and inflammation and has a high mortality rate. Previous studies have demonstrated that tripartite motif 59 (TRIM59) was involved in NF-κB signaling and could promote phagocytosis of macrophages, but the role of TRIM59 in sepsis is still unknown. In our study, we found that TRIM59 was downregulated in lipopolysaccharide (LPS)-stimulated bone marrow-derived macrophages (BMDMs). In the cecal ligation and puncture (CLP) sepsis mice model, the mortality of Trim59flox/floxLyz-Cre (Trim59-cKO) mice was higher, the immune cell infiltration and damage of liver and lung were more severe, and bacteria burden was increased. We also found that TRIM59 altered the production of pro-inflammation cytokines, as well as macrophage phagocytosis ability. Further analysis indicated that NF-κB signal pathway and Fcγ receptors might be involved in these regulations. Our study demonstrated for the first time that TRIM59 protects mice from sepsis by regulating inflammation and phagocytosis in macrophages.